[3H]Mazindol binding associated with neuronal dopamine uptake sites in corpus striatum membranes - Javitch, Jonathan (1983)
[3H]Mazindol labels neuronal dopamine uptake sites in corpus striatum membranes (KD = 18 nM) and neuronal norepinephrine uptake sites in cerebral cortex and submaxillary/sublingual gland membranes (KD = 4 nM). The potencies of various inhibitors of biogenic amine uptake in reducing [3H]mazindol binding in striatal membranes correlate with their potencies for inhibition of neuronal [3H]dopamine accumulation, whereas their potencies in reducing [3H]mazindol binding to cortical and salivary gland membranes correlate with their potencies for inhibition of neuronal [3H]norepinephrine accumulation. Similar to the dopamine and norepinephrine uptake systems, [3H]mazindol binding in all three tissues is dependent upon sodium (with potassium, lithium, rubidium, and Tris being ineffective substitutes) and chloride (with sulfate and phosphate being ineffective substitutes). In membranes of the cerebral cortex and salivary gland, half-maximal stimulation is observed at 50-80 mM NaCl, whereas in membranes of the corpus striatum half-maximal stimulation occurs at 240 mM NaCl. In striatal membranes NaCl increases the affinity of [3H]mazindol binding with no effect on the maximal number of sites. The enhancement of affinity is due to a selective slowing of the dissociation of the ligand from its binding site. The association of [3H]mazindol binding sites with neuronal dopamine uptake sites in the corpus striatum is further supported by the reduction of [3H]mazindol binding sites in striatal membranes following destruction of dopaminergic neurons by 6-hydroxydopamine. Similarly, the association of [3H]mazindol binding sites with neuronal norepinephrine uptake sites in cerebral cortex is supported by the reduction of [3H]mazindol binding to cortical membranes following destruction of noradrenergic neurons by N-(2-chloroethyl)-N-ethyl-2-bromobenzylamine.